Regularity Criterion for Weak Solution to the 3D Micropolar Fluid Equations - Yu-Zhu Wang; Zigao Chen (Journal of Applied Mathematics)
Regularity criterion for the 3D micropolar fluid equations is investigated. We prove that, for some T>0, if ∫0T∥vx3∥Lϱρdt<∞, where 3/ϱ+2/ρ≤1 and ϱ≥3, then the solution (v,w) can be extended smoothly beyond t=T. The derivative vx3 can be substituted with any directional derivative of v.